Outbreak of Stem Rust in Afforested Chir Pine in the Himalayas - Shukla, A. N.; Pandey, P. C. (Indian Forester, 1993)
The paper deals with the current status of stem rust of chir caused by Cronartium himalayense. On the basis of recent surveys conducted in the afforested sites in Tehri and Pauri Garhwal districts, it is concluded that the rust is again gaining epidemic proportions. Strategies to control the rust have been discussed with particular reference to a Cladosporium sp. hyperparasitic on telial columns of C. himalayense formed on its primary host Swertia spp.